The Italian Labor Market : Recent Trends, Institutions, and Reform Options - Schindler, Martin (Washington, D.C. : International Monetary Fund, 2009)
Despite improvements in labor market performance over the past decade, owing in part to past reforms, Italy's employment and productivity outcomes continue to lag behind those of its European peers. This paper reviews Italy's institutional landscape and labor market trends from a cross-country perspective, and discusses possible avenues for further reform. The policy discussion draws on international reform experience and on simulations based on a calibrated labor market matching model. A key lesson is that the details of reform design, and the sequencing of reforms, matter greatly for labor market outcomes and for the fiscal costs associated with these reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet